Wall function treatment for bubbly boundary layers at low void fractions - SOARES,DANIEL V. (2018)
Abstract The present work investigates the role of different treatments of the lower boundary condition on the numerical prediction of bubbly flows. Two different wall function formulations are tested against experimental data obtained for bubbly boundary layers: (i) a new analytical solution derived through asymptotic techniques and (ii) the previous formulation of Troshko and Hassan (IJHMT, 44, 871-875, 2001a). A modified k-e model is used to close the averaged Navier-Stokes equations together with the hypothesis that turbulence can be modelled by a linear superposition of bubble and shear induced eddy viscosities. The work shows, in particular, how four corrections must the implemented in the standard single-phase k-e model to account for the effects of bubbles. The numerical implementation of the near wall functions is made through a finite elements code.